Transmembrane Segment 6 of the Glut1 Glucose Transporter Is an Outer Helix and Contains Amino Acid Side Chains Essential for Transport Activity - Mueckler, Mike (American Society for Biochemistry and Molecular Biology, 2008)
Experimental data and homology modeling suggest a structure for the exofacial configuration of the Glut1 glucose transporter in which 8 transmembrane helices form an aqueous cavity in the bilayer that is stabilized by four outer helices. The role of transmembrane segment 6, predicted to be an outer helix in this model, was examined by cysteine-scanning mutagenesis and the substituted cysteine accessibility method using the membrane-impermeant, sulfhydryl-specific reagent, p-chloromercuribenzene-sulfonate (pCMBS). A fully functional Glut1 molecule lacking all 6 native cysteine residues was used as a template to produce a series of 21 Glut1 point mutants in which each residue along helix 6 was individually changed to cysteine. These mutants were expressed in Xenopus oocytes, and their expression levels, functional activities, and sensitivities to inhibition by pCMBS were determined. Cysteine substitutions at Leu(204) and Pro(205) abolished transport activity, whereas substitutions at Ile(192), Pro(196), Gln(200), and Gly(201) resulted in inhibition of activity that ranged from ∼35 to ∼80%. Cysteine substitutions at Leu(188), Ser(191), and Leu(199) moderately augmented specific transport activity relative to the control. These results were dramatically different from those previously reported for helix 12, the structural cognate of helix 6 in the pseudo-symmetrical structural model, for which none of the 21 single-cysteine mutants exhibited reduced activity. Only the substitution at Leu(188) conferred inhibition by pCMBS, suggesting that most of helix 6 is not exposed to the external solvent, consistent with its proposed role as an outer helix. These data suggest that helix 6 contains amino acid side chains that are critical for transport activity and that structurally analogous outer helices may play distinct roles in the function of membrane transporters.